More than just a Long Paddock: Fostering native vegetation recovery in Riverina Travelling Stock Routes and Reserves. (January 2017) - Davidson, Ian; O'Shannassy, Peter
Abstract : Travelling Stock Reserves provide the most significant networks of natural habitat in the New South Wales Riverina. Substantial biodiversity gains at two sites over 10 years inspired similar works on more than 200 reserves with high levels of demonstrable change occurring.